Fundamental transverse mode operation of a type‐II vertical‐external‐cavity surface‐emitting laser at 1.2 µm. Issue 2 (1st January 2017) - Möller, C.; Zhang, F.; Fuchs, C.; Berger, C.; Rehn, A.; Ruiz Perez, A.; Rahimi‐Iman, A.; Hader, J.; Koch, M.; Moloney, J.V.; Koch, S.W.; Stolz, W.
Abstract : The modal properties of a novel vertical‐external‐cavity surface‐emitting laser with (GaIn)As/Ga(AsSb)/(GaIn)As type‐II quantum wells are analysed. The device, emitting at a wavelength around 1175 nm, is operated in TEM00 mode and optimised for a high beam quality. The M 2 factors are measured at various pump powers. An excellent beam quality is observed for up to 350 mW with an M 2 < 1.2.